The Identification of Capital Transfers in the Balance of Payments - Bame, Jack (IMF Working Papers; Working Paper ;, 1995)
The separate identification of current and capital transfers was introduced for the first time in the fifth edition of the Fund's Balance of Payments Manual (Manual), thus harmonizing with the treatment of transfers in the 1993 System of National Accounts (1993 SNA). Capital transfers are now recorded in the capital account component of the balance of payments and include debt forgiveness, migrants' transfers, and other transfers, of which investment grants is a significant category. This paper presents the criteria for defining capital transfers and provides sources and methods of compilation, and examples of treatment, as illustrated in the Fund's Balance of Payments Compilation Guide and Balance of Payments Textbook.